Case reportsDifficulties connected with diagnosis of Melkersson-Rosenthal syndrome – case report - Jakubowicz, Oliwia; Żaba, Ryszard; Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Melkersson-Rosenthal syndrome is a rarely occurring disease, characterized by the triad of symptoms: recurrent orofacial swelling, relapsing facial palsy, and fissured tongue and wrinkles of tongue (lingua plicata). The aetiology of the disease has not yet been explained. Infectious factors, inheritance as well as allergic and immunological factors are considered in the aetiopathology of this syndrome. It is estimated that the syndrome affects less than 1% of the population, mainly young adults between 20 and 30 years of age, but it can appear regardless of age. Melkersson-Rosenthal syndrome is diagnosed all over the world. The classical form of this syndrome with the complete triad of clinical symptoms is observed rarely (8-25% of patients). Incomplete and monosymptomatic variants are dominant. This paper presents a 69-year old patient, with suspicion of Melkersson-Rosenthal syndrome and granuloma fissuratum diagnosed in the process of our investigations. The outcomes of laboratory research, specialist consultancy and applied treatment are presented.